REINSURANCE FORM THE PERSPECTIVE OF PROPERTY INSURANCE CONTRACT - Dănilă Ștefan MATEI (Challenges of the Knowledge Society)
The most significant means by which insurance markets operate to spread risks beyond like risk pools is reinsurance. The reinsurance operation has the advantage that the original insured can increase his financial capacity in order to cover the risks that he cannot bear alone. The risks are therefore spread and the danger of insolvency or of decreasing the financial capacities either disappears or is reduced. The reinsurance involves a new insurance, carried out by a new policy, for the same original insured risk, for the purpose of compensating the insured persons for the previously concluded insurances. Both contracts exist at the same time. By reinsurance the reinsurer receives reinsurance premiums, in return for which it contributes, according to the obligations assumed, to bearing the indemnities that the reinsured pays on the occurrence of the risk subject to reinsurance; the reinsured cedes reinsurance premiums, in return for which the reinsurer contributes, according to the obligations assumed, to bearing the indemnities that the reinsured pays on the occurrence of the risk subject to reinsurance. The reinsurance does not terminate the insurer’s obligations and does not establish any legal relationship between the insured and the reinsurer. This paper offers an introduction to key features of reinsurance, and some of the sources of complexity in the legal issues that arise